Ishikawa iteration process with errors for nonexpansive mappings - Jialin Huang (International Journal of Mathematics and Mathematical Sciences)
We study the construction and the convergence of the Ishikawa iterative process with errors for nonexpansive mappings in uniformly convex Banach spaces. Some recent corresponding results are generalized.